Living Values Education Dan Implikasinya Bagi Pendidikan Agama Kristen - Karlito D Markes (Sekolah Tinggi Teologi Arastamar Bengkulu, 2020)
Education is a process of inheriting life values ​​that serve as a guideline as well as a foundation for character development. Education must be a conscious and planned process and oriented to contextual life values. Living Values Education is one of the patterns education based on life values is deemed sufficiently relevant to Christian Education as a learning process about the living values of Christianity. The Bible explicitly records that the life, teachings, and role model of the Lord Jesus have practiced the Living Values ​​Education as a pattern of education. This research was conducted using the Literature Review method, through literature obtained both manually and also through an electronic database such as Google and Google Scholer. From the literature analysis conducted, this study found three principles as the basis for character development through The Christian Living Values ​​Education. First, the values ​​of human life with God. Second, the values ​​of human life with others. And third, the values ​​of human life by itself. All three values ​​of life have the same substance, namely: love with heart, soul, and mind. The hope of this research is that Christian religious educators are held on the values of life centered on Christ.